The Design of medium PRF radar schedules for optimum detectability in diverse clutter scenes - Alabaster, Clive M.; Hughes, Evan J. (IEEE, 2009)
Airborne fire control radars using medium pulse repetition frequency (PRF) waveforms are required to maintain good target detectability in various clutter scenes. This paper describes work to optimise PRF values of 3 of 8 medium PRF schedules in varying clutter scenes in order to achieve optimal target detectability. To this end, the detectability map is introduced as a means of illustrating and quantifying target detectability over the full Range/Doppler space of interest. The paper concludes that optimised PRF sets achieve similar detectability performances irrespective of the clutter scene.
Department of Aerospace, Power and Sensors, Cranfield Defence and Security, Cranfield University 2006